The gendered context of women charged with violent offences in the forensic psychiatric setting - Nagdee, Mohammed; Artz, Lillian; Subramaney, Ugasvaree; Young, Charles; Pieterse, Amanda; Pettitt, Julia (The South African journal of psychiatry, 2024)
BackgroundWomen charged with violent offences may be referred by courts for forensic psychiatric assessment to determine whether mental disorder or intellectual disability impacts their fitness to stand trial and/or criminal responsibility. The profile of these women is a poorly researched area in South Africa.AimThis study examined the socio-demographic, offence-related, and clinical profile of South African women charged with violent offences referred for forensic assessment.SettingFort England Hospital (FEH), a forensic psychiatric institution in the Eastern Cape.MethodsThe clinical records of 173 women referred by courts for forensic psychiatric evaluation over a 24-year period (1993–2017) to FEH were systematically reviewed.ResultsMost women were single, black mothers with dependent children, who were unemployed and socio-economically impoverished. Many had backgrounds of pre-offence mental illness, alcohol use and alleged abuse. The majority were first-time offenders whose victims were known to them. Most child victims were biological children killed by their mothers. Likely primary motives for violence were related to psychopathology in half of cases, and interpersonal conflict in a third. Forensic assessment most frequently confirmed psychotic disorders and dual diagnoses. Half the cases were fit to stand trial and under half were criminally responsible.ConclusionViolent female offending occurs within a gendered context, with high rates of prior trauma, alcohol use and psychosocial distress in perpetrators. An emphasis on gender-sensitive psychosocial interventions is required.ContributionThis study highlights the nature and context of violent offending by women referred for forensic psychiatric assessment in South Africa.